2021
DOI: 10.1007/s00127-021-02174-x
|View full text |Cite
|
Sign up to set email alerts
|

Social factors and the prevalence of social isolation in a population-based adult cohort

Abstract: Purpose Social isolation has negative effects on physical and brain health across the lifespan. However, the prevalence of social isolation, specifically with regard to sociodemographic and socioeconomic factors, is not well known. Methods Database was the Leipzig population-based study of adults (LIFE-Adult Study, n = 10,000). The short form of the Lubben Social Network Scale (LSNS-6) was used to assess social isolation (cutoff < 12 points). Sampling w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 46 publications
7
38
5
Order By: Relevance
“…Interestingly, the middle-aged (40–59 years old) group exhibits the lowest LSNS-6 values, yielding an “U”-shaped curve of LSNS-6 scores, as shown in Fig. 1 a and d. In our data data, 29.54% of the individuals aged 50–59 years old report being socially isolated, a figure significantly larger than what has been previously presented in the literature prior to the pandemic 30 .
Figure 1 Average LSNS-6 ( a ), LSNS-6 Friends ( b ) and LSNS-6 Family ( c ) scores per age group.
…”
Section: Resultssupporting
confidence: 37%
See 2 more Smart Citations
“…Interestingly, the middle-aged (40–59 years old) group exhibits the lowest LSNS-6 values, yielding an “U”-shaped curve of LSNS-6 scores, as shown in Fig. 1 a and d. In our data data, 29.54% of the individuals aged 50–59 years old report being socially isolated, a figure significantly larger than what has been previously presented in the literature prior to the pandemic 30 .
Figure 1 Average LSNS-6 ( a ), LSNS-6 Friends ( b ) and LSNS-6 Family ( c ) scores per age group.
…”
Section: Resultssupporting
confidence: 37%
“…Beyond Spain, a recent German study analysed social isolation data from a sample of 9392 adults (aged 18–79 years old) collected between August 2011 and November 2014. It reports a prevalence of social isolation in their sample of 12.3% 30 . The average LSNS-6 score in their sample was 17.6 ( ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The total score ranged from 0 to 30 points, with higher scores indicating a larger social network and <12 points indicating SI. An LSNS-6 score of <12 points varied strongly related to sociodemographic and socioeconomic factors [ 24 ], while the score predicted depression and the development of poor physical capability [ 25 ]. The Cronbach α coefficient of the LSNS-6 for our data in phase 1 was .859.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of loneliness in the general population has ranged from 10% to 27% in the United States, Europe, and Japan [2,3]. A cross-sectional study in Germany revealed that approximately 5.4% of adults aged 18-39 years were socially isolated [4]. Loneliness and social isolation negatively impact mental and physical health and wellbeing, increasing the consumption of health care resources and affecting economic development by reducing employee health [5].Recent studies have shown that about 4 out of 10 American physicians of different specialties report some degree of loneliness [6,7].…”
mentioning
confidence: 99%